2014
DOI: 10.1093/cid/ciu702
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Open-Label Clinical Study of Combined Pegylated Interferon Alfa-2a (40KD) and Entecavir Treatment for Hepatitis B "e" Antigen-Positive Chronic Hepatitis B

Abstract: Neither ETV add-on nor ETV pretreatment demonstrated superiority compared with 48 weeks of peg-IFN alfa-2a monotherapy. The optimal treatment strategy using nucleos(t)ide analogues and peg-IFN alfa-2a remains to be determined. Clinical Trials Registration. NCT00614471.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 31 publications
3
87
1
1
Order By: Relevance
“…Theoretically, combining an immune modulator with an NA is a very logical strategy for cure of viral hepatitis B. However, clinical trials combining peginterferon with lamivudine, adefovir or entecavir did not yield superior results as compared to peginterferon monotherapy . In a more recent clinical trial, combining peginterferon with tenofovir disoproxil fumarate for 1 year was shown to associate with a higher cumulative rate of HBsAg loss (9.1%) vs peginterferon monotherapy (2.8%) at 24‐week post‐treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, combining an immune modulator with an NA is a very logical strategy for cure of viral hepatitis B. However, clinical trials combining peginterferon with lamivudine, adefovir or entecavir did not yield superior results as compared to peginterferon monotherapy . In a more recent clinical trial, combining peginterferon with tenofovir disoproxil fumarate for 1 year was shown to associate with a higher cumulative rate of HBsAg loss (9.1%) vs peginterferon monotherapy (2.8%) at 24‐week post‐treatment .…”
Section: Discussionmentioning
confidence: 99%
“…62 pretreatment with NA improves the rates of sustained response to PegIFNa. 130,132,133 The multicentre ARES study demonstrated that a 24-week course of PegIFNa, given to a small group of HBeAg-positive patients who were on ETV therapy for only 24 weeks, can improve the kinetics of HBeAg, HBV DNA and HBsAg, compared to those on ETV monotherapy, but a PegIFNa monotherapy arm was missing. 134 In CHB patients under long-term effective virological remission by NA treatment, PegIFNa can be used as a 'switch to' or 'add-on' strategy.…”
Section: Na Plus Pegifna Recommendationsmentioning
confidence: 99%
“…HBeAg seroconversion at 24 weeks post treatment was 25-31% across all three groups and no significant differences were found with regards to response. Thus, the addition of entecavir to IFN in this study was not associated with apparent benefit [27].…”
Section: Hepatitis B E Antigen-positive Diseasementioning
confidence: 63%
“…HBsAg levels above 20 000 IU/ml at 12 weeks or no decline in HBsAg at 12 weeks (in comparison with baseline level) are associated with a very low probability of achieving HBeAg seroconversion, and thus treatment should be stopped [2]. HBeAg levels have been measured in a few studies, and low HBeAg levels are associated with greater likelihood of HBeAg seroconversion [27][28][29].…”
Section: On-treatment Predictors Of Responsementioning
confidence: 99%